2000
DOI: 10.1128/mcb.20.2.713-723.2000
|View full text |Cite
|
Sign up to set email alerts
|

A GATA Box in the GATA-1 Gene Hematopoietic Enhancer Is a Critical Element in the Network of GATA Factors and Sites That Regulate This Gene

Abstract: A region located at kbp ؊3.9 to ؊2.6 5 to the first hematopoietic exon of the GATA-1 gene is necessary to recapitulate gene expression in both the primitive and definitive erythroid lineages. In transfection analyses, this region activated reporter gene expression from an artificial promoter in a position-and orientationindependent manner, indicating that the region functions as the GATA-1 gene hematopoietic enhancer (G1HE). However, when analyzed in transgenic embryos in vivo, G1HE activity was orientation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
147
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(153 citation statements)
references
References 36 publications
4
147
2
Order By: Relevance
“…This suggested that the -16.5 ECR element can potentially play an important role in in vivo CCL2 transcriptional regulation. We found the enhancer activity exhibited by the -16.5 ECR to be orientation-dependent, which deviates from the operational definition of an enhancer (42)(43)(44). However, enhancers that are orientation-dependent for their function have previously been reported (45,46).…”
Section: Discussioncontrasting
confidence: 47%
“…This suggested that the -16.5 ECR element can potentially play an important role in in vivo CCL2 transcriptional regulation. We found the enhancer activity exhibited by the -16.5 ECR to be orientation-dependent, which deviates from the operational definition of an enhancer (42)(43)(44). However, enhancers that are orientation-dependent for their function have previously been reported (45,46).…”
Section: Discussioncontrasting
confidence: 47%
“…In Vivo" Footprint in GATA HS1-DNA fragments from the HS1 region of the mouse GATA-1 gene have been shown previously to have enhancer activity, when linked to the GATA-1 promoter alone or in combination with HS2 and other GATA-1 regulatory elements, in transient transfections, and in transgenic assays (13)(14)(15)(16). The activity of HS1 is totally dependent on a strong GATA-1-binding site (14 -16) that appears to be occupied in vivo, as indicated by in vivo footprinting (14).…”
Section: An "mentioning
confidence: 99%
“…Constructs including the mouse GATA-1 promoter up to a DNase I-hypersensitive site lying at about Ϫ700 nts 1 (HS2) are expressed, at low efficiency, in adult hematopoietic cells in transgenic mice but not in yolk sac cells; however, constructs including an additional more upstream site (HS1) are much more efficient and are also active in primitive hematopoietic cells (12)(13)(14)(15)(16). GATAbinding sequences in HS1 and HS2 are essential for activity in a variety of constructs, suggesting GATA-1 auto-regulation (8 -10, 14 -16); however, a GATA-1 transgenic construct is active in mice lacking the endogenous GATA-1 gene, suggesting that other members of the GATA family of transcription factors (possibly GATA-2) may control GATA-1 transcription (13,16). As GATA-2 is expressed in a wider range of cell types than GATA-1, this implies that other regulatory elements are necessary for appropriate GATA-1 regulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of regions critical for GATA-1 expression in erythroid cells and megakaryocytes have been identified by transgenic reporter experiments and targeted deletions in mice, and are summarized in figure 3. A genomic region that includes DNase 1 hypersensitive site lies approximately 3.5 kilobases upstream of the IE exon and can direct expression in primitive and definitive erythroid precursors and megakaryocytes, and has been referred to as an upstream enhancer (69)(70)(71). The large GATA-1 first intron contains exon IB and is important for definitive hematopoiesis, particularly in specifying expression in erythroid cells and megakaryocytes (72;73).…”
Section: Regulation Of the Gata-1 Locus In Mast Cellsmentioning
confidence: 99%